Sucrose-induced hyperglycemia dysregulates intestinal zinc metabolism and integrity: risk factors for chronic diseases - Mitchell, Samuel Blake; Hung, Yu-Han; Thorn, Trista Lee; Zou, Jiaqi; Baser, Filiz; Gulec, Sukru; Cheung, Celeste; Aydemir, Tolunay Beker (Frontiers in Nutrition, 2023)
Objective: Zinc is an essential micronutrient that is critical for many physiological processes, including glucose metabolism, regulation of inflammation, and intestinal barrier function. Further, zinc dysregulation is associated with an increased risk of chronic inflammatory diseases such as type II diabetes, obesity, and inflammatory bowel disease. However, whether altered zinc status is a symptom or cause of disease onset remains unclear. Common symptoms of these three chronic diseases include the onset of increased intestinal permeability and zinc dyshomeostasis.The specific focus of this work is to investigate how dietary sources of intestinal permeability, such as high sucrose consumption, impact transporter-mediated zinc homeostasis and subsequent zinc-dependent physiology contributing to disease development.We used in vivo subchronic sucrose treatment, ex vivo intestinal organoid culture, and in vitro cell systems. We analyze the alterations in zinc metabolism and intestinal permeability and metabolic outcomes.We found that subchronic sucrose treatment resulted in systemic changes in steadystate zinc distribution and increased 65 Zn transport (blood-to-intestine) along with greater ZIP14 expression at the basolateral membrane of the intestine. Further, sucrose treatment enhanced cell survival of intestinal epithelial cells, activation of the EGFR-AKT-STAT3 pathway, and intestinal permeability.Our work suggests that subchronic high sucrose consumption alters systemic and intestinal zinc homeostasis linking diet-induced changes in zinc homeostasis to the intestinal permeability and onset of precursors for chronic disease.